The legal argumentation viewed from disagreements in law (2018)
Being the legal reasoning inherit from theories of judicial decision and therefore from legal theory, it comes as fields of action the analysis of how the problems of post positivist legal theory affect the moments of justification of judicial decision. In this way it’s postulated for the present: The relation legal reasoning –theory of law, the binomial validity– applicability of legal norms, the moments of justification of judicial decision and the ways in which the legal reasoning related with disagreements between lawyers.